A Child with Acute Hemiparesis: A Case Report - Md Aris, Mohd Aznan; Wan Mansur, Wan Najwa Aima (Science Forecast Publications, 2021)
This is a case of an eight years old boy initially presented with right sided hemiparesis. His diagnosis was Moyamoya disease and been treated conservatively at initial stage. This disease is recurrent in nature, and the patient developed another stroke episode within 3 months. He was referred to neurosurgical team and was planned for a revascularization surgery for a better long-term outcome.